Syntheses, structures, and magnetic properties of two series of copper-lanthanide heterometallic coordination polymers based on pyridine-2, 3-dicarboxylic acid and succinic acid. Issue 4 (6th January 2017) - Zhang, Ju-Wen; Li, Xiao-Li; Kan, Xiao-Min; Wu, Hao; Liu, Ying; Liu, Bin-Qiu
Abstract : Two series of copper-lanthanide heterometallic coordination polymers have been successfully synthesized and structurally and magnetically characterized. Abstract : Two series of copper-lanthanide heterometallic coordination polymers (CPs), [LnCu(2, 3-pydc)2 (suc)0.5 (H2 O)3 ]·H2 O [Ln = La (I ), Pr (II ), Nd (III ), Sm (IV ), Gd (V ), and Eu (VI ), 2, 3-H2 pydc = pyridine-2, 3-dicarboxylic acid, H2 suc = succinic acid], [Ln2 Cu3 (2, 3-pydc)6 (H2 O)10 ]·8H2 O [Ln = Eu (VII ), Tb (VIII ), Dy (IX ), and Er (X )], [Ln2 Cu(2, 3-pydc)2 (suc)(μ2 -OH)2 (H2 O)2 ]·2H2 O [Ln = Er (XI ), Yb (XII ), and Lu (XIII )], [Ln2 Cu(2, 3-pydc)2 (suc)2 (H2 O)6 ]·2H2 O [Ln = Sm (1 ), Eu (2 ), Gd (3 ), Tb (4 ), Dy (5 ), and Er (6 )], and Ln2 Cu(2, 3-pydc)2 (suc)2 (H2 O)2 [Ln = Er (7 ), Yb (8 ), and Lu (9 )], were successfully synthesized by the hydrothermal reactions of Cu(NO3 )2 ·3H2 O, LnCl3 · n H2 O, 2, 3-H2 pydc, and H2 suc. CPs1–9 show two types of similar two-dimensional (2D) structures. In1–9, the 2, 3-pydc anions bridge the Cu II ions into a one-dimensional (1D) loop chain, and the suc anions link the Ln III ions into a 1D double chain. The 1D loop chains and the 1D double chains connect each other to generate a 2D layer. The adjacent 2D layers are further packed into a three-dimensional (3D) supramolecular architecture by hydrogen-bonding interactions. CPs4 and6 display ferromagnetic interactions between the paramagnetic centers, and CP5 shows a field-induced slow magnetic relaxation behavior. The structures and magnetic properties ofI –XIII have been reported in previous work ( Eur. J. Inorg. Chem., 2016, 1060).